2018
DOI: 10.2196/jmir.7802
|View full text |Cite
|
Sign up to set email alerts
|

Mode Equivalence of Health Indicators Between Data Collection Modes and Mixed-Mode Survey Designs in Population-Based Health Interview Surveys for Children and Adolescents: Methodological Study

Abstract: BackgroundThe implementation of an Internet option in an existing public health interview survey using a mixed-mode design is attractive because of lower costs and faster data availability. Additionally, mixed-mode surveys can increase response rates and improve sample composition. However, mixed-mode designs can increase the risk of measurement error (mode effects).ObjectiveThis study aimed to determine whether the prevalence rates or mean values of self- and parent-reported health indicators for children and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 64 publications
(80 reference statements)
1
9
0
Order By: Relevance
“…In order to benefit from this cost advantage to some extent without increasing the risk of nonresponse bias, the web mode could be integrated in a mixed-mode design. This approach, in which some respondents complete the questionnaire on the web and other respondents (ie, those unwilling/incapable to participate online) use another mode, is already being tested and used in multiple European HISs [ 44 - 46 ]. A specific mixed-mode methodology, push-to-web, could, for example, be considered: people would first be invited by postal mail to participate online and they would then be contacted by an interviewer only in case of nonparticipation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to benefit from this cost advantage to some extent without increasing the risk of nonresponse bias, the web mode could be integrated in a mixed-mode design. This approach, in which some respondents complete the questionnaire on the web and other respondents (ie, those unwilling/incapable to participate online) use another mode, is already being tested and used in multiple European HISs [ 44 - 46 ]. A specific mixed-mode methodology, push-to-web, could, for example, be considered: people would first be invited by postal mail to participate online and they would then be contacted by an interviewer only in case of nonparticipation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surveys are considered mode equivalent when participants give the same responses to the same questions administered by different modes . Previous reports showed that such differences were minimal between online and paper surveys, even when respondents had to report sensitive behaviours …”
Section: Advantagesmentioning
confidence: 99%
“…Active data collection processes have been shown to improve prevention programs and increase evaluative capacity to address multiple public health problems [ 14 – 17 ]. A robust data collection system for OEI was determined to have the following characteristics: 1) multimodality of data collection [ 17 – 20 ], 2) a standardized data model [ 21 23 ], and 3) systematic educational outreach efforts to train those reporting data [ 24 – 26 ]. These characteristics are supported by literature recommending tailored data collection systems created with evaluation in mind, followed by capacity building and training for these data collection systems [ 15 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The final data are electronic, and paper forms have additional data entry and submission steps; however, many of the community organizations do not have the technology to collect data online, and it may be easier to collect data on paper during in-person visits with participants. Prior research indicates improved data quality when multiple data collection modes are available [ 17 – 20 ].…”
Section: Introductionmentioning
confidence: 99%